2001
DOI: 10.1042/cs1000661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoking on levels of bioavailable testosterone in healthy men

Abstract: The effect of smoking on androgen levels is important given the recent interest in the link between low levels of androgens and the development of cardiovascular disease. Numerous studies examining the effects of cigarette smoking on the levels of total and free testosterone have reported conflicting findings, but there has been no accurate assessment of the effects of cigarette smoking on the levels of bioavailable testosterone [not bound to sex hormone-binding globulin (SHBG)]. We attempted to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
21
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 31 publications
11
21
5
Order By: Relevance
“…Similarly, we found that testosterone showed inverse correlations with fibrinogen, HsCRP, uric acid, white blood cell, and smoking. The results of previous studies describing the effects of cigarette smoking on testosterone levels in human males have been conflicting, and no significant effect on the biologically active fraction of testosterone has been shown, but smoking may influence the levels of total and free testosterone through changes in the levels of sex hormones binding globulin (27). The main difference between these findings and our findings may be related to the selection and characteristics of the patient population.…”
Section: Discussioncontrasting
confidence: 80%
“…Similarly, we found that testosterone showed inverse correlations with fibrinogen, HsCRP, uric acid, white blood cell, and smoking. The results of previous studies describing the effects of cigarette smoking on testosterone levels in human males have been conflicting, and no significant effect on the biologically active fraction of testosterone has been shown, but smoking may influence the levels of total and free testosterone through changes in the levels of sex hormones binding globulin (27). The main difference between these findings and our findings may be related to the selection and characteristics of the patient population.…”
Section: Discussioncontrasting
confidence: 80%
“…Although, some authors have reported lower [18] or similar [19] testosterone levels in healthy male smokers compared to non-smokers, most authors have found higher levels of total and free testosterone [10][11][12]. As SHBG levels also are increased in smoking men, it has been suggested that the increase in testosterone levels is a consequence of the increased SHBG levels.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, testosterone supplementation has been found to improve lean body mass and body composition in men with COPD [7][8][9]. It is generally agreed that smoking is strongly associated with reduction in pulmonary function, and in several cross-sectional studies smoking has been associated with higher both total and free testosterone levels [10][11][12]. Thus, there are several strong and interesting relationships between testosterone levels and pulmonary functions, but to our knowledge no large population-based study has investigated these associations.…”
Section: Introductionmentioning
confidence: 80%
“…Several studies have explored this relationship, reporting higher T concentrations in current smokers [13][14][15]. The mechanism is unclear but it has been postulated that smoking may have a centrally mediated effect on the axis, or may act indirectly by increasing SHBG concentrations, thereby increasing circulating T [13][14][15]. Smoking itself is a powerful risk factor for respiratory ill-health including from chronic obstructive pulmonary disease (COPD) and lung cancer [16].…”
Section: Introductionmentioning
confidence: 97%